Memantine, an antagonist of the NMDA glutamate receptor, affects cell proliferation, differentiation and the intracellular cycle and induces apoptosis in Trypanosoma cruzi. - Flávia Silva Damasceno; María Julia Barisón; Elisabeth Mieko Furusho Pral; Lisvane Silva Paes; Ariel Mariano Silber (PLoS Neglected Tropical Diseases)
Chagas' disease is caused by the protozoan parasite Trypanosoma cruzi and affects approximately 10 million people in endemic areas of Mexico and Central and South America. Currently available chemotherapies are limited to two compounds: Nifurtimox and Benznidazole. Both drugs reduce the symptoms of the disease and mortality among infected individuals when used during the acute phase, but their efficacy during the chronic phase (during which the majority of cases are diagnosed) remains controversial. Moreover, these drugs have several side effects. The aim of this study was to evaluate the effect of Memantine, an antagonist of the glutamate receptor in the CNS of mammals, on the life cycle of T. cruzi. Memantine exhibited a trypanocidal effect, inhibiting the proliferation of epimastigotes (IC50 172.6 µM). Furthermore, this compound interfered with metacyclogenesis (approximately 30% reduction) and affected the energy metabolism of the parasite. In addition, Memantine triggered mechanisms that led to the apoptosis-like cell death of epimastigotes, with extracellular exposure of phosphatidylserine, increased production of reactive oxygen species, decreased ATP levels, increased intracellular Ca(2+) and morphological changes. Moreover, Memantine interfered with the intracellular cycle of the parasite, specifically the amastigote stage (IC50 31 µM). Interestingly, the stages of the parasite life cycle that require more energy (epimastigote and amastigote) were more affected as were the processes of differentiation and cell invasion.